Investigation of the Adequacy of Bridge Design Loads in Pakistan - Shahid, I; Noman, A. K.; Farooq, S. H.; Arshad, Ali (Indonesian Journal of Science and Technology, 2019)
Weight, configuration, and volume of traffic vary from country to country. But, in developing countries like Pakistan, bridges are designed based on codes of developed countries. Hence, these bridges may not have desired safety level. In this study, safety levels of three sample bridges has been investigated in terms of structural reliability index.Â  Live load effects (shear and moments) in girders were determined using weigh-in-motion data (WIM) and were extrapolated to 75 years using non-parametric fit. Two live load models and two strengths, required by 1967 Pakistan Code of Practice for Highway Bridges (PHB Design-Case) and that required by the 2012 AASHTO LRFD Bridge Design Specifications (AASHTO Design-Case) were used in reliability analysis. It is found that actual trucks produce moment and shear in girders 11 to 45 percent higher than live load models of PHB and AASHTO design cases. Values of structural reliability indices vary from 1.25 to 2.50 and from 2.45 to 3.15 for PHB and AASHTO design cases, respectively, and are less than the target reliability index value of 3.50 used in the design codes as benchmark.Â  It is revealed after the research that bridges in Pakistan may not have desired safety level, and current live load models may not be the true representation of service-level truck traffic.